EMILIUSZ PAULUS W PODRÓŻY PO GRECJI - Appel, Hanna (In Gremium. Studies in History, Culture and Politics, 2018)
Following the Battle of Pydna, the victorious general Lucius Aemilius Paullus embarked on a trip of Greece. Accounts of the event may be found in Polybius, Livy and Plutarch. Each of them focused on different aspects of that journey. The most extensive surviving report is provided in Livy’s Ab Urbe Condita (45, 27-28), which is therefore the basic reference for the analysis conducted by the author in this paper. Her particular focus is on the fragments which describe Aemilius’ visits to Delphi and Olympia, and his reaction to works of Greek masters. The author compares the above ancient accounts, which show that Aemilius’ trip could be perceived as a continuation of a military action (Polybius), an inspection conducted by a victorious general (Plutarch), or simply an educational voyage of an enthusiast of Greek art, but also a pious person who would offer proper sacrifice to gods wherever his journey brought him (Livy).